Characteristics Of Learning In The Independent Learning Curriculum In Madrasah Ibtidaiyah - R. Lawson, Emily; Harper, Linda V. (Universitas Islam Zainul Hasan Genggong, 2025)
The independent learning curriculum is one of the steps chosen by the government as the restoration of education in Indonesia after the Covid 19 polemic several years ago. As learning development and innovation, the independent learning curriculum offers learning concepts namely independent thinking, independent innovation, independent independent and creative learning. There are three main elements that characterize the independent learning curriculum as will be described in this paper. These three characteristics include; 1) Pancasila character, in its application in the form of project-based learning for the development of soft skills and characters according to the profile of Pancasila students 2) Competency-based, namely focusing on essential material so that there is sufficient time for in-depth learning of basic competencies such as literacy and numeracy. 3) Flexible Learning, meaning flexibility for teachers to carry out differentiated learning according to the abilities of students and make adjustments to the context and local content.